2018
DOI: 10.1186/s13063-018-2647-y
|View full text |Cite
|
Sign up to set email alerts
|

Administration of taurolidine-citrate lock solution for prevention of central venous catheter infection in adult neutropenic haematological patients: a randomised, double-blinded, placebo-controlled trial (TAURCAT)

Abstract: BackgroundCatheter-related bloodstream infection (CRBSI) is one of the most frequent complications in patients with cancer who have central venous catheters (CVCs) implanted and is associated with substantial morbidity and mortality. Taurolidine is a non-antibiotic agent with broad-spectrum antimicrobial activity, which has been used as a lock solution to prevent CRBSI in some settings. However, little is known about its usefulness in high-risk adult neutropenic patients with cancer. This prospective randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(50 reference statements)
0
6
0
1
Order By: Relevance
“…Given the infectious diseases, the formation of clots and fibrinous pods, catheter dysfunction is expected, since these issues limit their life span (15,18). Although various strategies have been considered, including heparin, antibiotics and solution, to reduce the incidence of catheter-induced infection (11,20,21), so far there is no approach to prevent catheter dysfunction and catheter-related infections, especially in people with long-term use of the catheter. However, some studies have suggested the role of thrombolytic drugs in preventing catheter inappropriate functioning (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the infectious diseases, the formation of clots and fibrinous pods, catheter dysfunction is expected, since these issues limit their life span (15,18). Although various strategies have been considered, including heparin, antibiotics and solution, to reduce the incidence of catheter-induced infection (11,20,21), so far there is no approach to prevent catheter dysfunction and catheter-related infections, especially in people with long-term use of the catheter. However, some studies have suggested the role of thrombolytic drugs in preventing catheter inappropriate functioning (19).…”
Section: Discussionmentioning
confidence: 99%
“…Given the important role of central venous catheters in hemodialysis patients, administration of the accumulated solutions to these catheters is an important option for the prevention and treatment of catheter-related infections (4,21).…”
Section: Discussionmentioning
confidence: 99%
“…This study has been registered in ISRCTN under identifier ISRCTN47102251. The study protocol (31) can be accessed at https://www.isrctn.com/search?qϭISRCTN47102251. The information on this trial is reported in accordance with CONSORT recommendations (see Text S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Sendo o profissional de enfermagem, além de legalmente apto à sua inserção 8 , o componente da equipe que mais permanece em contato com esse público no manejo dos cuidados factíveis à prática resolutiva e qualificada, torna-se incontestável o seu profundo envolvimento com uma tecnologia tão emergente. Todavia, assim como acessos centrais tradicionais, a utilização do PICC associa-se, ainda, a uma considerável incidência de Eventos Adversos (EAs), com destaque às complicações infecciosas e trombóticas 9,10 .…”
Section: -4829unclassified